Changes in habitat selection patterns of the gray partridge Perdix perdix in relation to agricultural landscape dynamics over the past two decades. Issue 9 (3rd April 2019) - Harmange, Clément; Bretagnolle, Vincent; Sarasa, Mathieu; Pays, Olivier
Abstract: Changes in agricultural practices have reshaped agricultural landscapes and triggered a drastic decline in spatial and temporal heterogeneity leading to changes in habitat quality and food resources for birds. However, the precise relationships between landscape changes, spatial and temporal heterogeneity, and habitat preferences in response to those changes remain poorly known. We investigated patterns of habitat selection and causes for changes over the years 1997–2017 for the gray partridge Perdix perdix, an iconic farmland species which has experienced a severe decline since the 1950s. Using a long‐term (1997–2017) dataset collected over 435 km 2, we modeled relationships between annual land‐cover maps and partridge sightings over 17 5‐year moving windows, assessing the effects of landscape metrics, the strength of the relationships, and the dynamics of habitat suitability. We detected a shift in gray partridge habitat preferences over time, toward more risky habitats. Avoidance of predator reservoirs (woodlands and buildings) has weakened, and selection of human infrastructure, such as roads and tracks, has increased. Since 1997, the mean size of suitable patches has also decreased by about 26%. We have interpreted these changes in habitat selection as being the result of decreasing habitat quality and the increasing prevalence of captive‐reared birds, currently released in their thousands in the study site. Synthesis and applications . The gray partridge has not adjusted well to changes in farming practices, and the low, still decreasing, population density suggests that it is not sustainable, despite local initiatives and the investment in captive‐bird releases. We emphasize that efforts must be redirected toward habitat improvement to restore the density of refuge cover, insects, and seeds in the landscape, hunting management to ensure self‐sustainable populations and massive releases of high‐quality birds. Only integrated local management, involving hunters, farmers, gamekeepers, and scientists can ensure the recovery of this species. Abstract : Our results revealed a shift in gray partridge habitat preferences over time, toward more risky landscape features. Avoidance of predator reservoirs (woodlands and buildings) has weakened, and selection of human infrastructure, such as roads and tracks, has increased.